Rhino-orbital-cerebral mucormycosis caused by Rhizopus arrhizus diagnosis via metagenomics next-generation sequencing: a case report - Li, Jianhong; Ge, Yuwen; Xin, Chengqi; Jiang, Li (Frontiers in Cellular and Infection Microbiology, 2024)
Rhino-orbital-cerebral mucormycosis (ROCM) is a rare, invasive, and fatal fungal disease, which is often to be easily misdiagnosed in the early stage due to the lack of specific clinical manifestations and adequate auxiliary examinations. Early diagnosis and timely therapy are essential for successful treatment. In this report, we presented a 46-year-old man with diabetic, who experienced gradual vision loss and right ptosis, swelling, and headache, and progressively worsened to death within four days after admission. It was finally confirmed as a fungal Rhizopus arrhizus infection by metagenomics next-generation sequencing (mNGS). Our report has proved that mNGS testing should be strongly recommended in highly suspected patients.